Mobile application of nutrition information on malay breakfast (NIMB) / Muhammad Khairuddin Abd. Mutalib - Muhammad Khairuddin, Abd. Mutalib (2011)
The purpose of this project is to introduce a mobile based application to help people gained information on their daily breakfast meal in order for them to eat a balance breakfast meal that is ideal for their health and BMI. This project use secondary data from the internet sources, articles and books to collect data. This project is implemented in mobile hand phones that supports Java and uses Symbian as it platforms. The main functions of the application are the food information where user can gained useful information and nutrition facts from this and also ingredients information where user can gained details information about the ingredients in the breakfast meal in order for user to maintain a balanced diet. The result of using the application shows that, many people agree that this application can help them in managing their diet and the food information that they received are accurate. In future, the application will be added with more function so people can really find it more useful and can guide people in making decision for what are really best for them. The application can be also implemented in other platform and fully functional with touch phones.